Disciplina áulica y su repercusión en el rendimiento escolar de los estudiantes de la Escuela de Educación Básica “Dr. Francisco Javier Martínez Aguirre” del cantón Vinces provincias de los Ríos. - Plaza Zerna, Alexis María (2018)
This research project aims to know the repercussion in the classroom discipline and the school performance of the students of the third year of basic education of the school "Dr. Francisco Martínez Aguirre” del canton Vinces, province of los Rios. For this reason, the present research establishes the repercussion of the classroom discipline in the academic performance of the student, leading to investigate the reasons why this great problem that afflicts the educational institutions occurs. The difficulty of achieving coherent and harmonious interaction in the students to whom the teachers do not understand their actions proposes to establish the analysis and monitoring of said situation. This study establishes the areas of interaction that affect the classroom discipline that causes low school performance in students in the third year of basic education of the DR school. Francisco Martinez Aguirre " Del canton Vinces, province of los Rios, this situation afflicts almost all educational institutions because the established norms and regulations are not clear. It started from the recognition of the shortcomings; detected through the application of instruments such as surveys applied to parents of families, students and teachers, the answers were analyzed, determining the main errors to improve student learning. and above all to determine actions that allow improving the classroom discipline. In the didactic workshops is intended to apply, monitor and meet the perspectives arising during their management and consequently the group under study, will be the one that allows us to establish consistent parameters in the acquisition of our proposal this acquires pedagogical elements of great value that allow it have a better education. The classroom discipline requires attention and acquires relevance when it influences academic performance.